Antibacterial Effect Of Muntingia Calabura L. Leaf Extract To Pseudomonas Aeruginosa - Anggono, Yovita; Jong, F.X. Himawan H.; Rahayu, Titien (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2019)
Background: Pseudomonas aeruginosa is an opportunistic pathogen which can cause infection in every part of the human body lacking normal defense. This bacteria is one of the leading cause of nosocomial infection in Indonesia. Treating infection caused by Pseudomonas aeruginosa is now more challenging due to its resistance to many classes of antibiotics. On the other hand, Muntingia calabura L. is a genus of plants in the family Elaeocarpaceae, which is spread widely throughout South East Asia, including Indonesia. Some of the researches in the past show antibacterial properties of these plants. Aim: to determine the antibacterial effect of Muntingia calabura L. Leaf extract to Pseudomonas aeruginosa. Method: This research is an experimental study using in vitro technique and non-equivalent control group design. The method used in this study was microdilution in 96-well microplate and concentrations of Muntinga calabura L. Leaf extract used in this study were 50-800mg/mL. Minimum Inhibitory Concentration (MIC) was measured by a spectrophotometer, while Minimum Bactericidal Concentration (MBC) was observed by direct streaking to the agar plate. Result: MIC value was found at the concentration range of 400-800 mg/mL, while MBC was found at concentration 800 mg/mL. Conclusion: There is a potential bactericidal effect of Muntingia calabura L. To Pseudomonas aeruginosa